2011
DOI: 10.1088/0004-637x/728/2/154
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons and the Diffuse Interstellar Bands: A Survey

Abstract: We discussthe proposalrelating the origin of someof the diffuse interstellar bands (DIBs) to neutral and ionized polycyclic aromatic hydrocarbons(PAHs) presentin interstellar clouds. Laboratory spectra of severalPAHs, isolated at low temperature in inert gas matrices, are comparedwith an extensiveset of astronomical spectra of reddened,early type stars. From this comparison,it is concludedthat PAH ions are good candidatesto explain someof the DIBs.Unambiguousassignmentsare difficult, however,dueto the shift in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 43 publications
3
154
0
Order By: Relevance
“…They range from 0.8 × 10 12 cm −2 for anthracene to 1 × 10 14 cm −2 for phenanthrene. Similar upper limit values for PAHs were derived by Salama et al (2011).…”
Section: Gas-phase Studiessupporting
confidence: 84%
“…They range from 0.8 × 10 12 cm −2 for anthracene to 1 × 10 14 cm −2 for phenanthrene. Similar upper limit values for PAHs were derived by Salama et al (2011).…”
Section: Gas-phase Studiessupporting
confidence: 84%
“…The DIBs are a set of several hundred absorption features spanning the wavelength range of the near ultraviolet (UV) at λ 4000Å (e.g., see York et al 2006, Gredel et al 2011, Salama et al 2011, Bhatt & Cami 2015 to the near infrared (IR) at λ 1.8 µm (e.g., see Joblin et al 1990, Geballe et al 2011, Cox et al 2014, Zasowski et al 2015, Hamano et al 2015, with most of the bands falling in the visible wavelength range. The DIBs were originally discovered in 1919 by Herger (1922) and their interstellar nature was established based on their stationary nature as observed toward spectroscopic binaries.…”
Section: Introductionmentioning
confidence: 99%
“…Many possible carriers have been proposed, ranging from grain impurities and exotic molecules to H 2 . In the past two decades the field has converged towards larger carbonaceous molecules, like the fullerenes and polycyclic aromatic hydrocarbons (PAHs), which have electronic transitions in the optical (see for example Salama et al 1999;Ruiterkamp et al 2005;Kokkin & Schmidt 2006;Zhou et al 2006;and Salama et al 2011). New diffuse bands have been detected in one line-of-sight which appear to match with naphthalene and anthracene cations (Iglesias-Groth et al 2008 and the weak 5450 Å DIB is found to match with an absorption band arising from a hydrocarbon plasma created in the laboratory (Linnartz et al 2010).…”
Section: Introductionmentioning
confidence: 99%